Representasi Bullying dalam Drama My Nerd Girl Season 1 - Nabila Salsa Widya (Abstrak : Jurnal Kajian Ilmu seni, Media dan Desain, 2025)
The phenomenon of bullying among teenagers is an increasing and complex social problem, not only occurring in everyday life but also widely represented through mass media, one of which is teen drama. One popular media that highlights this issue is My Nerd Girl Season 1, which shows the reality of bullying in its various forms. The main character, Rea, is depicted as a victim of bullying who experiences verbal, emotional, and social pressure from her environment. This representation illustrates that bullying is not just an individual act, but part of a social construction that is full of meaning. This study aims to explore how bullying is presented in the drama My Nerd Girl Season 1 using Roland Barthes's semiotic approach. The analysis focuses on the denotative, connotative, and mythical meanings contained in the visual and narrative symbols in the bullying scenes. The research data in the form of scene clips showing forms of bullying, are then analyzed to reveal the underlying social ideology. The results show that this drama represents bullying in various forms, ranging from verbal, cyber, physical, to social. These bullying acts are presented as a form of power, domination, and group control over individuals. The emerging connotative meanings indicate that bullying is legitimized by adolescent ideologies regarding popularity, physical appearance standards, and social acceptance in the school environment. The myth constructed through the drama's narrative is that symbolic and social violence is often considered normal or even necessary to maintain a certain social status. Thus, My Nerd Girl Season 1 serves not only as entertainment but also as a medium for social reflection that reveals the reality of bullying among adolescents.